Ocular Trauma in Children - Israr Ahmed Bhutto, Abdul Sami Memon, Sadia Bukhari, PS Mahar, Umair Qidwai (Pakistan Journal of Ophthalmology, 2011)
Purpose: To evaluate the causes of ocular trauma, management and visual outcome in children. Materials and Methods: This prospective observational case series was conducted at the Department of Pediatric Ophthalmology, Isra Postgraduate Institute of Ophthalmology / Al-Ibrahim Eye Hospital, Karachi from November 2009 to October 2010. All patients of Ocular trauma aging less than 15 years were included in the study. Results: A total number of 173 children (174 eyes) presented with ocular trauma from November 2009 to October 2010. Minimum age of presentation was 2 months, while the maximum age was 180 months with mean of 97.172 months (SD = 41.82). Out of total number of children, 125 (72.25%) were male and 48 (27.75%) were female. Blunt mode of trauma was the most frequently observed mode of injury among children and was, seen in 88 (50.6%) patients. The causes included Vegetative material in 25 (14.4%) and wooden stick in 23 (13.2%) patients. Fifty four (31%) patients were treated surgically while rest of the patients was treated medically. Most common cause of decreased vision was disorganized globe seen in 21 (12.1%) patients followed by corneal opacity in 18 (10.3%) patients. Conclusion: Pediatric ocular trauma is a common cause of ophthalmic consultation. These injuries are mainly result of the blunt trauma. Majority of patients are young boys. There is a need for increasing awareness among parents.